Students' Perception and Challenge on Online Learning during Pandemic : EFL Senior High School Speaking Learning Context - Melani, Ester (Universitas Negeri Surabaya, 2022)
Speaking learning in EFL classes must be carried out online during the Covid-19 pandemic in Indonesia. This study investigates students' perceptions of learning speaking in online EFL classes during the pandemic. This study usedmixed method with quantitative and qualitative,likert scale questionnaire as well as interviews with open-ended questions to 72students of class X SMA in Surabaya, East Java who have applied online speaking learning in EFL classes. The results revealthat students perceiveonline EFL learning is difficult to understand, and do notsupport the application of speaking learningwith its own challenges such as connection problem, less students’ learning motivation, and the difficulties to find the appropriate method and platform to practice speaking. However, they also perceive that in this learning, teachers do their best to deliver EFL learning materials by choosing methods and materials that are considered easier to understand.